IDENTIFIKASI ARAH REMBESAN DAN LETAK AKUMULASI LINDI DENGAN METODE GEOLISTRIK RESISTIVITAS DI TEMPAT PEMBUANGAN AKHIR (TPA) TAMANGAPA MAKASSAR - Rosdiana, Rosdiana; Said L, Muh; Rahmaniah, Rahmaniah (Universitas Islam Negeri Alauddin Makassar, 2015)
This research aimed to identify the location of accumulation and distribution direction of the spread of leachate at landfills Tamangapa around Makassar Multichannel Resistivity meter resistivity measurements using the form of the voltage injected into the subsurface through a predetermined trajectory as much as six trajectory. The method used is Geolistrik resistivity method with Wenner-Schlumberger configuration. Data processing is done by using RES2DINV to generate a 2D cross-section of data below the surface, and use Voxler 3 to determine distribution direction and location of the accumulation of leachate seepage of leachate . Based on the location of the results obtained by the accumulation of leachate generated from landfill waste decomposition Tamangapa Makassar interpreted to be at a depth of 2.50-18.52 m with apparent resistivity values from 0.0090-5.00 Î©m at coordinates 5017'727''LS and 119049'084''BT elevation 16-20 m above sea level. While the distribution of leachate seepage direction around Tamangapa Makassar interpretation in sector 1 seepage eastward direction which is at coordinates 5017'594''LS and 119049'202''BT with a depth of 2.50-12.80 m. In the second sector is interpreted towards see page of leachate to the west which is at coordinates 5017'727''LS and 119049'084''BT with a depth of 2.50-31.87 m.